COVID‐19‐related posttraumatic stress disorder in adults with lived experience of psychiatric disorder. Issue 7 (10th May 2022) - Lewis, Catrin; Lewis, Katie; Roberts, Alice; Evison, Claudia; Edwards, Bethan; John, Ann; Lloyd, Keith; Pearce, Holly; Poole, Rob; Richards, Natalie; Robinson, Catherine; Jones, Ian; et al.
Abstract: Background: Prevalence estimates of COVID‐19‐related posttraumatic stress disorder (PTSD) have ranged from 1% to over 60% in the general population. Individuals with lived experience of a psychiatric disorder may be particularly vulnerable to COVID‐19‐related PTSD but this has received inadequate attention. Methods: Participants were 1571 adults with lived experience of psychiatric disorder who took part in a longitudinal study of mental health during the COVID‐19 pandemic. PTSD was assessed by the International Trauma Questionnaire (ITQ) anchored to the participant's most troubling COVID‐19‐related experiencevent. Factors hypothesised to be associated with traumatic stress symptoms were investigated by linear regression. Results: 40.10% of participants perceived some aspect of the pandemic as traumatic. 5.28% reported an ICD‐11 PTSD qualifying COVID‐19 related traumatic exposure and 0.83% met criteria for probable ICD‐11 COVID‐19‐related PTSD. Traumatic stress symptoms were associated with younger age, lower income, lower social support, and financial worries, and lived experience of PTSD/complex PTSD. Depression and anxiety measured in June 2020 predicted traumatic stress symptoms at follow‐up approximately 20 weeks later in November 2020. Conclusions: We did not find evidence of widespread COVID‐19‐related PTSD among individuals with lived experience of a psychiatric disorder. There is a need for future research to derive valid prevalence estimates of COVID‐19‐related PTSD.